Minimizing Work Accidents in the Shipyarding Industry Using JSA and HAZOP Methods - Oktavianus, Sandi; Waruwu, Arniwika; Sembiring, Anita Christine (Department of Industrial Engineering - Universitas Yudharta Pasuruan, 2022)
PT. Cahaya Baru Shipyard is a company engaged in ship repair. Activities in shipyards have various risks, one of which is work accidents. The research aims to determine the risk of work accidents from shipbuilding activities, risk control and suggestions for improvement. This study identifies risks using the Job Safety Analysis (JSA) method and assisted by the Hazard And Operability Study (HAZOP) method to control potential hazards and recommendations for new safety systems to minimize work accidents. The research method used is qualitative. The results of the study show that most work accidents occur in welding and cutting activities with a percentage of 23.3%. Providing personal protective equipment and workers reminding each other to use safety equipment and to remain careful in doing their work, implementing standard operating procedures (SOPs) and existing work instructions can be a way that can be done to minimize work accidents.